Pengaruh Tingkat Pendidikan, Tingkat Pengangguran, Dan Tingkat Kemiskinan Terhadap Ketimpangan Pendapatan Di Kabupaten Jombang - Tarrisma Delvy Andini; Mohamad Fathur Rohman; Muchtar . (CV. ITTC INDONESIA, 2026)
Income inequality is a crucial issue in regional economic development. This is because income inequality can affect social and economic stability and hinder sustainable economic growth. In Jombang Regency, income inequality remains a serious problem. This study aims to analyze the influence of education level, unemployment rate, and poverty rate on income inequality in Jombang Regency using a positivistic approach through quantitative methods. Secondary data were obtained from official BPS publications and regional macroeconomic indicators, while the analysis was conducted using multiple linear regression supported by classical assumption tests to ensure that the model meets BLUE criteria. The results show that the education level has a negative and significant effect on income inequality, indicating that higher levels of education lead to lower income disparities. Conversely, the unemployment rate and poverty rate have positive and significant effects, suggesting that increases in unemployment and poverty contribute to widening income inequality in the region. Simultaneously, all three variables are proven to significantly influence income inequality, as reflected by the coefficient of determination, which demonstrates the strong contribution of the independent variables in explaining variability in income disparity. This study is expected to provide both theoretical and practical contributions to the formulation of inclusive and equitable economic development policies.